Improved Hole Extraction Selectivity of Polymer Solar Cells by Combining PEDOT:PSS with WO3. Issue 12 (17th October 2021) - Sokeng Djoumessi, Aurelien; Alam, Shahidul; Madalaimuthu, Jose Prince; Anand, Aman; Slowik, Josef; Pflug, Theo; Meitzner, Rico; Roesch, Roland; Gnecco, Enrico; Horn, Alexander; Schubert, Ulrich S.; Hoppe, Harald
Abstract : As the device performance and stability of polymer solar cells strongly depend on the interfacial charge extraction layers, the hole transport layer (HTL) properties are crucial. Furthermore, unfavorable interactions with the electrode or the photoactive layer should be screened and prevented. Organic solar cells of conventional architecture by varying the HTL material and layer stack systematically between PEDOT:PSS and a sol–gel‐derived tungsten oxide (WO3 ) are investigated. The impact of various HTLs in the solar cells is investigated by optical and electrical characterization. Interestingly, a triple‐layer WO3 /PEDOT:PSS/WO3 configuration results in the best device performance specifically compared with the use of pristine WO3 and pristine PEDOT:PSS hole extraction layers. The triple layer also shows an increased reproducibility in the lifetime, which, combined with the improvement in the efficiency, can be the keys for expectable revenue. Abstract : Herein, the effect of a sol–gel‐derived tungsten oxide (WO3 ) solution, used as passivated layer in a triple‐layer WO3 /PEDOT:PSS/WO3 configuration, is discussed. The device shows better contact selectivity and blocking behavior compared with the PEDOT:PSS‐based device, resulting in the best device performance and increased reproducibility in the lifetime.